Biodegradability assessment of cork polymer composites for sustainable packaging applications - Lisete Garrido Moutinho; Eduardo Soares; Martinho Oliveira (Next Materials)
A dramatic challenge for the environment is the sharp rise in fossil-based plastic waste, which is brought on by increased consumption of these materials in large scale, and by a poor waste management system globally. Therefore, it is worth to think about how to contribute to solve this issue. As a result, biodegradable polymers emerged, preserving some useful qualities of conventional polymers but able to biodegrade under certain conditions without damaging the environment. Biodegradable polymers present some drawbacks in terms mechanical performance that can be mitigated by the use on natural fillers resulting in biocomposites. This work presents a study on the biodegradability of poly(lactic acid) (PLA) based cork polymer composites (CPC) intended for sustainable packaging applications. CPC biocomposites were subjected to 12 weeks of soil burial test (SBT) and the samples were analyzed before and after 7 and 12 weeks of SBT. Morphological inspection, Fourier transform infrared spectroscopy (FTIR) analysis, weight loss monitoring, contact angle measurements and gel permeation chromatography were conducted to characterize the samples and their evolution under degradation conditions. The results obtained indicate that cork has an influence on the degradation profile of the PLA polymeric matrix. CPC presenting lower degradation signs. This effect might be relevant for the lifespan of PLA based biocomposites on packaging materials during shelf-life and use.